Incidencia del comportamiento del comercio internacional del sector azucarero en la ocupación de Colombia y el Valle del Cauca (2021)
This study presents an analysis to determinate the correlation between Colombian sugar imports and exports respect of occupation in Colombian and Valle del Cauca department. This research wants to identify the impact on social and economic development. This paper has done a historical analysis of the variables to establish the data that allow applying two econometric models of multiple linear regression, whose results allow to identify the statistics significance level in Colombia and Valle del Cauca employe respect the sugar international trade. The results shows a low significative level between the dependent and independent variables.